The arthritis cure : the medical miracle that can halt, reverse, and may even cure osteoarthritis - Theodosakis, Jason
By outlining a nine-point program that includes a new effective supplement, ASU, this book describes a program that can halt, reverse, and possibly even cure degenerative osteoarthritis.--From publisher description.